LAYANAN INFORMASI TENTANG KESEHATAN REPRODUKSI PADA REMAJA PUTRI ANGGOTA PANTIASUHAN AISYIAH I KOTA BARAT BANJARSARI SOLO - Sri Suryanti, Hera Heru (Lembaga Penelitian dan Pengabdian Masyarakat, 2018)
The purpose of community service activities with the theme of Information Service on Reproductive Health in Young Women Aisyiah I orphanage member West City Banjarsari Solo is to provide knowledge about reproductive health in young women members of Putri Aisyiah I West Kota, Banjarsari, Solo in order to take care of themselves and prepare self as a prospective mother.The target of this community service activity is the realization of the guidance to maintain the health of femininity that can be used by young women members of Orphanage Princess Aisyiah I West Town, Banjarsari, Solo. So that helps the achievement of the goal effectively and efficiently is able to maintain the health of her feminine in a preventive and correct so that become healthy citizens.This community service is implemented by applying Brenstorming method, Lecture method, Question answer method, and Exercise method to make the material easy to receive and practiced completely by the members. Information service is conducted for one month with frequency of exercise once a week, place of execution at Princess Orphanage Aisyiah I Solo. Through this activity the members have knowledge about reproduction health, so as to strengthen the self-adolescent girls who entered the orphanage and finally the young women become members of a strong and productive society.Keywords: Information services, reproductive health.